Enabling efficient edge intelligence: a hardware-software codesign approach - Huai, Shuo (Nanyang Technological University, 2023)
Deep Neural Networks (DNNs) have made significant advancements in various domains, including computer vision (CV), natural language processing (NLP), etc. With the Internet of Things (IoT) and edge computing rapidly developing, edge intelligence, which brings computing services closer to the user, has become a key technique for mitigating latency issues and addressing privacy concerns of accessing cloud servers. To enhance the efficiency (i.e., high accuracy and high throughput) of edge intelligence, in this thesis, we optimize it from three fundamental and indispensable aspects: algorithms, training data, and computing hardware.